Experimental and theoretical approaches for electrical, magnetic, micromechanical, and structural characterization of BSCCO ceramic superconductors - Safran, S.; Ozturk, H.; Bulut, F.; Ozturk, O. (Elsevier BV, 2018)
Abstract This study investigates how the preparation and re-pelletization of BSCCO ceramic superconductors affects their structural, magnetic, electrical, and mechanical properties. Samples were prepared using conventional methods including the dry solid state (SS) reaction and wet ammonium nitrate (AN) precipitation, with three variations prepared for each technique. The fabricated samples were then characterized with X-ray powder diffraction (XRD) and scanning electron microscopy. The density, resistance vs. temperature characteristics, AC susceptibility vs. temperature characteristics, and magnetic hysteresis properties were measured. In addition, Vicker's microhardness was measured and revealed that all six samples exhibit the reverse indentation size effect (RISE). Microhardness modeling was also conducted. Calculations with Meyer's law, the Hays and Kendall model, and the proportional sample resistance model indicate that the samples are far from the plateau region, whereas the indentation-induced cracking model was consistent with the experimental results. The elastic modulus, Young's modulus, yield strength, and brittleness index were also calculated for each sample.
Keywords: 13. Climate action; 7. Clean energy